Reports on hospitals and the patient and a domestic workers' charter - Great Britain. Standing Joint Committee of Industrial Women's Organisations ; Labour Party (Great Britain). Advisory Committee on Public Health (London : Labour Party, 1931)
1931 1931 1930s 22 pages Three main reasons cause nursing to be unpopular as a profession :— (1.) The age at which probationers are required to start for training is eighteen (which is a reasonable age for such work), or even older. and there are waiting years after leaving school to fill in. This makes it difficult for a girl who has to earn her living. She must start on something else, and may not later on want to leave it. (2.) The hours are very long. (3.) It is impossible to provide for old age from the salaries paid. D. Paying Patients. A distinction is now growing up between paying and non-paying patients in hospitals. The payments are sometimes for private wards, and may be as high as six guineas a week, with medical fees in addition. For others there are often graded payments, running from 2s. 6d. upwards, according to income. These payments may sometimes be done away with altogether, irrespective of income, if the patients can secure a subscriber's letter. In London there are about 1,100 beds in paying wards, and some of these have been taken from wards that were originally established for the sick poor. Thus the system is very unfair in its working, and is rendered more so by the fact that the patients in the paying wards, and occasionally even paying patients, side by side with non-paying, may receive more attention than others. E. Representation of Working Women. There is a great need of working class representatives, and especially women, on the management committees of hospitals. This can be more easily met when they are under Public Health Authorities, but owing to the small number of working women on the Councils, is still far short of the need. It is often not realised that under the 1929 Act it is possible to co-opt women on to the governing bodies of municipal hospitals. On voluntary hospitals there are very rarely such representatives, and their need in supervising arrangements suitable to the patients is greatly felt. (6) 126/TG/RES/X/1036A/7